Social Support and Career Adaptability : A Study on Early Career Employees - Dheliana Rosalia Septyven; Sutarto Wijono (Philanthropy: Journal of Psychology, 2024)
Individuals entering the world of work will make various plans for their career planning process. Throughout their careers, individuals face challenges in adapting to their career task and responsibilities. This is known as career adaptability. This study aims to find out if there is a relationship between social support and career adaptability. This study used a quantitative approach with a simple correlational design. The population in this study were early career employees working in Salatiga City and the sample size was 52 participants. Data were collected using a combined technique of purposive sampling and snowball sampling. The scales used were the Multidimensional Perceived Social Support (α = 0.935) with 12 items and the Career Adaptability Scale (α = 0.920) with 22 items. Spearman's Rho correlation test showed that the value of r = 0.443 ; p < 0.05. It can be interpreted that social support is positively and significantly related to career adaptability in early career employees. This research is expecte to provide additional information for further research and may help companies to increase the career adaptability of their eemployees by providing social support. Keywords: Career Adaptability; Early Career; Employee; Social Support